2022
DOI: 10.3390/polym14030365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reinforcement Effect of Achatina fulica Snail Shell Nanoparticles, Montmorillonite, and Kaolinite Nanoclay on the Mechanical and Physical Properties of Greenpoxy Biocomposite

Abstract: This study investigated the comparative reinforcement effect of Achatina fulica snail shell nanoparticles, montmorillonite, and kaolinite nanoclay on greenpoxy. Greenpoxy nanocomposites of snail shell nanoparticles, montmorillonite, and kaolinite nanoclay were developed separately, with the nanofiller content ranging from 1 to 3% by weight. Specimens of the nanocomposites with different percentage weights of the nanoparticles were prepared using the resin casting method. Mechanical properties, such as the tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The predicted inhibition efficiency at these optimum conditions was 96.7%, and the experimental validation of the predicted value resulted in an inhibition efficiency of 96.5%, approximately near the predicted value, as depicted in Figure 4. The optimized conditions of temperature, concentration, and time were found to agree with the literature, which reported that a higher temperature and inhibitor concentration could increase the inhibition efficiency [13][14][15][16][17]. However, the graphs also showed that with an increase in time beyond a certain point apparently did not increase the inhibition efficiency.…”
Section: Design Of Experimentssupporting
confidence: 84%
See 1 more Smart Citation
“…The predicted inhibition efficiency at these optimum conditions was 96.7%, and the experimental validation of the predicted value resulted in an inhibition efficiency of 96.5%, approximately near the predicted value, as depicted in Figure 4. The optimized conditions of temperature, concentration, and time were found to agree with the literature, which reported that a higher temperature and inhibitor concentration could increase the inhibition efficiency [13][14][15][16][17]. However, the graphs also showed that with an increase in time beyond a certain point apparently did not increase the inhibition efficiency.…”
Section: Design Of Experimentssupporting
confidence: 84%
“…They were then dehydrated by drying in a low-temperature oven. Gbadeyan et al [13] describe a combination of mechanical and chemical approaches for producing nanoparticles. The dry AS was first ground in a ball milling machine.…”
Section: Syntheses Of Avocado Seed Nanoparticlesmentioning
confidence: 99%
“…These combinations were identified as optimum based on the actual concentration factor of 0.5 wt.% SBCF. Snail shell nanoparticles increase the interfacial bonding of SBCF and PLA, resulting in solid structures with better barrier properties against water permeability [ 36 , 37 , 38 ]. A similar inclination was observed in Figure 2 c for thermal stability, where a combination of 99.5 wt.% PLA, and 0.5 wt.% SBCF offered maximum thermal stability of 263 °C, indicating the optimal concentration of PLA and SBCF for higher thermo-physical properties of bioplastic films.…”
Section: Resultsmentioning
confidence: 99%
“…This performance implies that the nano-CaCO 3 in the bioplastic films was responsible for increasing the thermal stability temperature of PLA from 198 to 340 °C. This thermal performance can be attributed to the inherent thermal property of the incorporated nanoparticle 27,37 .…”
Section: Resultsmentioning
confidence: 99%